2009
DOI: 10.1073/pnas.0905264106
|View full text |Cite
|
Sign up to set email alerts
|

The cytochrome ba 3 oxygen reductase from Thermus thermophilus uses a single input channel for proton delivery to the active site and for proton pumping

Abstract: The heme-copper oxygen reductases are redox-driven proton pumps that generate a proton motive force in both prokaryotes and mitochondria. These enzymes have been divided into 3 evolutionarily related groups: the A-, B-and C-families. Most experimental work on proton-pumping mechanisms has been performed with members of the A-family. These enzymes require 2 proton input pathways (D-and K-channels) to transfer protons used for oxygen reduction chemistry and for proton pumping, with the D-channel transporting all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
185
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(202 citation statements)
references
References 45 publications
(42 reference statements)
14
185
1
Order By: Relevance
“…1), and then into the bulk aqueous phase. Finally, the structurally conserved water bridging propionate-A and propionate-D of the active-site heme have also been proposed to be the proton loading site (22,23), which is the model most favored by the results presented here.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…1), and then into the bulk aqueous phase. Finally, the structurally conserved water bridging propionate-A and propionate-D of the active-site heme have also been proposed to be the proton loading site (22,23), which is the model most favored by the results presented here.…”
mentioning
confidence: 80%
“…Essentially, one is left with the six histidine ligands to the metals, the four propionate side chains of the hemes, and conserved internal water molecules (23). Several models of proton pumping have focused on one or more of the histidine ligands to Cu B (24)(25)(26)(27)(28)(29), but no compelling evidence has emerged.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our results show that in the E25 P A and Q variants, even though the uptake of protons is severely slowed, it still occurs through the same path (from the inside), because the RCRs are still approximately 5 in the liposome-reconstituted E25 P A and Q variants. In the ba 3 HCuO from T. thermophilus, which belongs to the B family, it was also suggested that there is only one proton pathway spatially equivalent to the K pathway (17), and this pathway was shown to be used during the oxidation of the fully reduced enzyme (31) and also during reduction of the enzyme (17), supporting this pathway being the only functional proton pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The residues constituting the D pathway are missing in cbb 3 s and cbb 3 s presumably have only one pathway (3,16), spatially analogous to the K pathway in the A type, for delivering protons from the cytosol to the catalytic site. This feature is shared between the C-and B-type oxidases (17) and has been proposed to be linked to the lower pumping stoichiometry observed in these HCuOs (n ¼ 2 in 2) (1, 18). In NOR, both the D and the K pathways are missing, and protons are supplied from the periplasmic side of the membrane in a reaction that does not conserve the energy available from NO reduction (19,20).…”
mentioning
confidence: 99%